ANALISIS FAKTOR-FAKTOR PERILAKU KERJA YANG MEMPENGARUHI KINERJA SEKRETARIAT DINAS KOMUNIKASI DAN INFORMASI DAERAH ISTIMEWA YOGYAKARTA - Nur Azizah SW; Prihartanto Eko Wibowo (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2024)
ABSTRACK This research aims to determine the factors that influence the performance of the secretariat of the Yogyakarta Special Region Communication and Information Service. This research uses a quantitative method with a sample size of 25 samples. The sampling method uses non-probability sampling with the researcher's technique using saturated sampling. The results of this research are the regression equation from this research is Y = -3.345 + 0.142 (23,269 > 2,068), and sign value. 0.000 is smaller than 0.05 (0.000 < 0.05), this shows that variable factors influence the performance of the secretariat. Thus, the hypothesis that "it is suspected that there is an influence between Work Behavior (X) on the performance of the Secretariat (Y) at the Yogyakarta Special Region Communication and Information Service is declared accepted.